2016
DOI: 10.1016/j.chest.2016.08.1009
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis-Induced VTE: Is It a Safe Recreational Drug?

Abstract: INTRODUCTION: Cannabis is the most commonly used recreational drug in the United States. Its abuse has been associated with Coronary thrombosis, Myocardial Infraction (MI), Ischemic stroke and central retinal vein thrombosis. We report a case of Sub-massive Pulmonary Embolism (PE) in a young male following heavy cannabis smoking. CASE PRESENTATION: 35-year-old Male with history of Schizophrenia presented to ER with worsening pleuritic chest pain, SOB and pain in the right leg for few days. Other review of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Half of the patients in our study were either current or previous cigarette smokers, and 42% of these patients experienced a TEE while undergoing cisplatin-based chemotherapy. Cannabis is the most commonly used recreation drug in the United States and has been suggested to cause myocardial infarction and ischemic stroke[ 30 ]. Only a single case of PE in a young male following heavy cannabis use has been reported[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the patients in our study were either current or previous cigarette smokers, and 42% of these patients experienced a TEE while undergoing cisplatin-based chemotherapy. Cannabis is the most commonly used recreation drug in the United States and has been suggested to cause myocardial infarction and ischemic stroke[ 30 ]. Only a single case of PE in a young male following heavy cannabis use has been reported[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis is the most commonly used recreation drug in the United States and has been suggested to cause myocardial infarction and ischemic stroke[ 30 ]. Only a single case of PE in a young male following heavy cannabis use has been reported[ 30 ]. It has been suggested that cannabinoids, the active component of cannabis, cause endothelial cell disruption leading to vascular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical reports have associated cannabis use with thrombogenic development culminating into acute coronary artery disease. However, over the past decade, there have been many discrepancies concerning the influence of endocannabinoids on the formation of thrombus and platelet aggregation. While some studies indicate a cannabinoid-mediated procoagulating effect on human platelet cells, , additional research has shown that cannabinoids efficiently inhibit platelet aggregation. , …”
Section: Medicinal Prospect Of Cannabinoids In Vascular-related Patho...mentioning
confidence: 99%